2015
DOI: 10.1080/01488376.2015.1077187
|View full text |Cite
|
Sign up to set email alerts
|

Kinship Foster Care Among African American Youth: Interaction Effects at Multiple Contextual Levels

Abstract: This study investigated the effects of kinship foster care on mental health outcomes among African American youth. Longitudinal data were used from a nationally representative sample of children and adolescents who were the subject of child protective services investigation from 1999 to 2000 (n=5,501). The secondary analyses focused on African American youth (n=225) placed into foster care. In structured interviews, current caregivers reported on youth internalizing and externalizing behaviors immediately foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Overall, this study's findings contribute to the inconclusive literature regarding child outcomes by placement types. Prior research suggests that there are advantages and disadvantages to each placement type, and that there may few differences between placements in regard to child symptoms and functioning (Rufa and Fowler 2016). Although policy endorses kinship placements when out-of-home placement is deemed necessary, the only finding of the current study supporting this approach was that children in foster care were more frequently rated by clinicians as having PTSD compared to kinship care.…”
Section: Discussionmentioning
confidence: 52%
“…Overall, this study's findings contribute to the inconclusive literature regarding child outcomes by placement types. Prior research suggests that there are advantages and disadvantages to each placement type, and that there may few differences between placements in regard to child symptoms and functioning (Rufa and Fowler 2016). Although policy endorses kinship placements when out-of-home placement is deemed necessary, the only finding of the current study supporting this approach was that children in foster care were more frequently rated by clinicians as having PTSD compared to kinship care.…”
Section: Discussionmentioning
confidence: 52%
“…Child welfare agencies may now be more aware of the importance of supporting racial/ethnic identity among youth of color and have focused on recruiting more foster families of color and relying more on kinship care (Schwartz, 2007). Black children are more likely to be placed in kinship care than other racial groups because of cultural assumptions, which were discussed earlier in this paper, and families' willingness to serve in this role (Rufa & Fowler, 2016). However, children in kinship care tend to have lower rates of reunification and adoption than those in nonrelated foster care; this is especially true for Black children (see review in Bell & Romano, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Faith communities' role in recruitment of foster and adoptive parents has been particularly noted (e.g., Barbell & Sheikh, 2000). When children are being placed permanently, kinship care is considered positively in part because the caregivers have a cultural and ethnic background similar to that of the child (Rufa & Fowler, 2016), yet in nonpermanent placements, cultural needs are seldom considered. Schatz and Horejsi (1996) noted that religion often is not mentioned during the home study and licensing process of foster parents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research has shown that the disproportionate placement of Black children in kinship care related to culture and familial willingness to provide support (e.g., existence of large extended family and fictive kin networks of support; Rufa & Fowler, 2015 ). Taking care of a relative’s child under extreme duress and devaluation has been a testament to the caring nature of Black families (Denby & Curtis, 2013 ).…”
Section: Black Children and Kinship Carementioning
confidence: 99%